Epidemiology's Role in the Creation of a Humane World: Convergences and Divergences Among the Schools: Editorial - Breilh Paz y Miño, Jaime Eduardo (1995)
This plea for changes in the way epidemiology is practiced presumes a progressive spirit among many readers, sharing a desire and in a position to serve humanity. The criteria used to begin this study of our role in the development of epidemiology is not simply a matter of technocratic formulae, but is based, rather on a committed point of view about the human dimension in the development of epidemiology. The aim is to generate propositions that will eliminate processes that destroy and threaten human life, promoting, instead, supportive measures and processes to protect society, the family and the individual.